Method for preparing test material, method for measuring diffusible hydrogen content, method for evaluating delayed fracture properties, method for selecting metallic materials, and method for manufacturing components
Patent Information
- Application Number
- JP2024560287
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-08-30
- Filing Date
- 2024-07-03
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-07-03
AI Technical Summary
【0017】 本開示によれば、溶接部を備える金属材料の拡散性水素量を精度高く測定できる試験材の作製方法を提供できる。 また、本開示によれば、上記試験材の作製方法で作製された試験材を用いた拡散性水素量の測定方法、遅れ破壊特性の評価方法、金属材料の選択方法、および部材の製造方法を提供できる。
Smart Images

Figure 0007609344000004 
Figure 0007609344000005 
Figure 0007609344000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for preparing a test material, a method for measuring a diffusible hydrogen content, a method for evaluating delayed fracture properties, a method for selecting a metallic material, and a method for manufacturing a component. [Background technology]
[0002] In recent years, from the viewpoint of preventing global warming, there has been a demand for improving energy efficiency, for example, gasoline fuel efficiency in the case of automobiles, by reducing the weight of moving objects such as automobiles, ships, and railway vehicles. Steel, one of the materials that make up moving objects, requires high strength in order to ensure the same level of safety as before, even when the plate thickness is reduced to reduce weight.
[0003] On the other hand, steel materials for automobiles are plastically worked into a desired shape by press forming and then assembled to the vehicle body by welding, for example, spot welding. Therefore, steel materials for automobiles are required to have not only press formability but also the ability to be properly welded in various sheet combinations.
[0004] However, the increase in the strength of steel materials has the problem of increased susceptibility to a phenomenon called delayed fracture. Delayed fracture is a phenomenon in which a metal material is subjected to a static load and, after a certain period of time, suddenly undergoes brittle fracture without any apparent plastic deformation. Here, this refers to hydrogen embrittlement-type fracture caused by the intrusion of hydrogen into the metal material.
[0005] Known factors influencing delayed fracture include the hydrogen embrittlement susceptibility of metal materials, applied load (e.g., residual stress), and the amount of hydrogen that penetrates into the metal material. For example, in the case of steel, when the strength of the steel increases, the hydrogen embrittlement susceptibility increases significantly, and even if the amount of hydrogen that penetrates into the steel is small, the steel will break (crack). In particular, hydrogen embrittlement susceptibility increases significantly in steel materials with a tensile strength of 1180 MPa or more (Non-Patent Document 1).
[0006] Therefore, even if the strength required for steel materials increases, the steel materials are required not to cause delayed fracture, i.e., to have excellent delayed fracture resistance. In particular, the welded parts of steel materials have higher strength than the base steel material, and therefore are more susceptible to hydrogen embrittlement. It has also been reported that delayed fracture occurs in metal materials other than steel materials.
[0007] Therefore, there is a need for a method for evaluating the delayed fracture properties of welds in metallic materials.For example, in the examples of Patent Document 1, a method for evaluating the hydrogen embrittlement properties of spot welds in steel sheets is disclosed in which a sheet is sandwiched between two plates with a thickness of 2 mm or 4 mm as spacers at both ends of the sheet, and the center between the spacers is joined by spot welding to prepare a test piece, which is then immersed in 0.5 mol / l sulfuric acid, hydrogen is introduced by an electric current, and the presence or absence of cracks is evaluated after 2 hours.
[0008] In addition, delayed fracture is said to be influenced by hydrogen (diffusible hydrogen) that penetrates into steel. Therefore, it is thought that it is possible to evaluate the delayed fracture properties of welds by measuring the upper limit of the amount of diffusible hydrogen (critical diffusible hydrogen amount) that does not cause delayed fracture in welds.
[0009] For example, Patent Document 2 discloses a method for measuring the amount of diffusible hydrogen, which is a cause of delayed fracture, in a welded joint of an actual structure with high accuracy. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2007-231373 A [Patent Document 2] JP2008-261821 Public Relations [Non-patent literature]
[0011] [Non-Patent Document 1] Matsuyama, Shinsaku: Delayed Fracture, Nikkan Kogyo Shimbun, Tokyo, (1989). Summary of the Invention [Problem to be solved by the invention]
[0012] When evaluating the delayed fracture properties of a welded portion of a metallic material using the method disclosed in Patent Document 1, it is necessary to perform a test for a specified time and determine whether a crack has occurred in the welded portion. However, because it is determined whether a crack has occurred in the welded portion at the specified time, test pieces in which a crack has occurred before the specified time and test pieces in which a crack has occurred at the specified time are evaluated on the same level, which poses a problem in that it is not possible to accurately evaluate the occurrence of cracks for each test piece.
[0013] In addition, using the method for measuring the diffusible hydrogen content of welded joints disclosed in Patent Document 2, the amount of diffusible hydrogen (amount of penetrated hydrogen) was measured for welds into which hydrogen had been introduced under the same conditions, and it was found that the measured hydrogen content values could differ significantly in some cases.
[0014] The present disclosure has been made in consideration of the above circumstances, and aims to provide a method for producing a test material that can measure the amount of diffusible hydrogen in a metal material having a welded portion with high accuracy.
[0015] In addition, the present disclosure aims to provide a method for measuring the amount of diffusible hydrogen using a test material produced by the above-mentioned test material production method, a method for evaluating delayed fracture properties, a method for selecting a metal material, and a method for producing a component. [Means for solving the problem]
[0016] As a result of extensive investigations, the present inventors have found that the above object can be achieved by employing the following configuration, and have completed the present invention. [1] A method for preparing a test material for measuring the amount of diffusible hydrogen in a metal material having a weld, comprising: A step of identifying a blowhole position in a test piece which is a metal material having a weld; a processing step of processing the blowhole identified in the step of identifying the blowhole position so that it does not have a closed structure, or of removing the blowhole. [2] A method for preparing a test material as described in [1], wherein the volume ratio of the weld metal in the test material is 50% or more. [3] A method for measuring the amount of diffusible hydrogen in a metal material having a weld, comprising: A hydrogen introduction step of introducing hydrogen into a test material prepared by the test material preparation method described in [1] or [2] above; A hydrogen amount measuring step of measuring the amount of hydrogen in the test material into which hydrogen has been introduced in the hydrogen introduction step. [4] A method for evaluating delayed fracture properties of a metallic material having a weld, comprising: A method for evaluating delayed fracture properties, comprising an evaluation step of evaluating delayed fracture properties based on the amount of diffusible hydrogen obtained by the method for measuring the amount of diffusible hydrogen described in [3] above. [5] A method for selecting a metal material, comprising the steps of: A method for selecting a metallic material, comprising a selection step of selecting a metallic material based on the delayed fracture property obtained by the delayed fracture property evaluation method described in [4] above. [6] A method for manufacturing a member, comprising the steps of: A method for manufacturing a component, comprising at least a welding step of manufacturing the component by welding a metal material selected by the method for selecting a metal material described in [5] above. Effect of the Invention
[0017] According to the present disclosure, a method for producing a test material can be provided that allows for highly accurate measurement of the amount of diffusible hydrogen in a metal material having a welded portion. In addition, according to the present disclosure, it is possible to provide a method for measuring the amount of diffusible hydrogen using a test material produced by the above-mentioned test material production method, a method for evaluating delayed fracture properties, a method for selecting a metal material, and a method for producing a component. [Brief description of the drawings]
[0018] [Figure 1]FIG. 1 is a schematic diagram illustrating an example of a method for extracting a test material from a metal material having a welded portion. [Diagram 2] FIG. 2 is a schematic diagram illustrating an example of a processing method in the processing step. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] As described above, the inventors have conducted extensive research into the problem of inability to obtain reproducibility for the amount of diffusible hydrogen in metal materials having welds using spot-welded steel materials, and have found that the above-mentioned method has the following problems.
[0020] A spot weld has a blowhole, which is an internal defect. When the spot weld is exposed to an environment where hydrogen penetrates (hydrogen penetration environment), a large amount of hydrogen accumulates in the blowhole. At this time, it is presumed that the hydrogen in the blowhole is gasified. The hydrogen accumulated in the blowhole is stable hydrogen, that is, non-diffusible hydrogen. According to Non-Patent Document 1, this non-diffusible hydrogen does not significantly affect the delayed fracture properties. However, the hydrogen accumulated in the blowhole may be forcibly desorbed in a hydrogen temperature-programmed desorption analysis and may be detected as diffusible hydrogen, so the amount of hydrogen that penetrates the weld (diffusible hydrogen amount) appears to increase. In addition, the amount of hydrogen accumulated in the blowhole varies depending on the blowhole size, so the measured hydrogen amount of the spot weld will also vary depending on the volume and number of the blowholes. However, it is difficult to control the size, shape, and number of blowholes with current welding technology.
[0021] Therefore, the inventors investigated the relationship between blowholes present in welds and the amount of hydrogen, and found that by eliminating blowholes with a closed structure, it is possible to accurately evaluate the amount of infiltrated hydrogen (amount of diffusible hydrogen) that infiltrates into the weld from the environment and affects delayed fracture.
[0022] The present disclosure has been made based on the above findings. Hereinafter, a method for preparing a test material for measuring the amount of diffusible hydrogen in a metallic material having a welded portion according to an embodiment of the present disclosure, a method for measuring the amount of diffusible hydrogen, a method for evaluating delayed fracture, a method for selecting a metallic material, and a method for manufacturing a component will be described. Note that the present disclosure is not limited to the following embodiments. In addition, the components in the following embodiments include those that are replaceable and easy for a person skilled in the art, or those that are substantially the same.
[0023] <How to prepare test materials> A method for preparing a test material for measuring the amount of diffusible hydrogen in a metallic material having a welded portion according to one embodiment of the present disclosure includes a step of identifying a blowhole position in the test material, which is a metallic material having a welded portion, and a processing step of processing the blowhole identified in the step of identifying the blowhole position so that it does not have a closed structure, or of removing the blowhole.
[0024] (metallic material) First, the metal material will be described. The metal material is not particularly limited as long as it is weldable and does not cause delayed fracture due to hydrogen. As described above, in the case of steel, hydrogen embrittlement susceptibility increases significantly when the tensile strength of the steel is 1180 MPa or more. Therefore, the metal material is preferably a high-strength steel sheet, particularly a steel sheet having a tensile strength of 1180 MPa or more. The metal material may be a plated steel sheet having the above-mentioned high-strength steel sheet as a base.
[0025] The metal material having a welded portion may be a welded metal material. Here, the welded portion is composed of a weld metal and a heat-affected zone.
[0026] The welding may be any of fusion welding (arc welding, laser welding, electron beam welding, plasma arc welding, etc.) and pressure welding (spot welding, projection welding, seam welding, etc.). For example, when spot welding is used as the welding method, the weld metal becomes the nugget portion.
[0027] It is preferable that the test material is prepared so that the volume ratio of the weld metal is 50% or more. Therefore, a method for preparing a test material according to an embodiment of the present disclosure may include a preparation step of preparing a test material containing a desired volume ratio of the weld metal. Hydrogen (diffusible hydrogen) that affects delayed fracture is absorbed in a larger amount in the weld metal than in the base metal and the heat-affected zone. Therefore, in order to appropriately evaluate the superiority or inferiority of the delayed fracture properties of a metallic material having a welded portion, it is preferable that the volume ratio of the weld metal in the test material is 50% or more. The volume ratio of the weld metal is more preferably 70% or more, further preferably 80% or more, and may be 100%.
[0028] The volume ratio of the weld metal in the test material may be adjusted, for example, when the test material is extracted from a metal material after welding (a metal material having a welded portion). FIG. 1 is a schematic diagram for explaining an example of an extraction method when extracting a test material from a metal material having a welded portion. In the preparation step, for example, as shown in FIG. 1, a test material 3 may be extracted from a metal material 1 having a welded portion so as to include a weld metal (nugget portion) 2. In this case, as described above, it is preferable to extract the test material 3 so that the volume ratio of the weld metal 2 is 50% or more. Examples of the extraction method include an extraction method using a microcutter or wire cut. In addition, in the preparation step, the volume ratio of the weld metal contained in the test material may be adjusted by adjusting the welding current or the like when welding the metal material.
[0029] In order to appropriately evaluate the delayed fracture properties of metallic materials having welds, it is preferable to match the volume ratio of the weld metal between test materials. When evaluating the delayed fracture properties of test materials, it is preferable to use test materials with a weld metal volume ratio within ±10%, and more preferably within ±5%.
[0030] (Step to identify blowhole location) In the step of identifying the blowhole position, the position of the blowhole present in the welded portion of the test material is identified. The method of identifying the blowhole position is performed by non-destructive testing, since it is necessary to identify the blowhole inside the welded portion, introduce hydrogen into the test material, and measure the amount of introduced hydrogen. Examples of the non-destructive testing include X-ray CT testing and ultrasonic flaw detection testing. In addition, by using images obtained by these tests, the volume ratio of the weld metal in the test material can also be evaluated.
[0031] (Processing steps) In the processing step, the blowhole identified in the step of identifying the blowhole position is processed so as not to have a closed structure, or the blowhole is removed. Examples of the method of processing so as not to have a closed structure include a process of providing a through hole T that connects the surface of the test material to the blowhole B as shown in FIG. 2(a), and a process of grinding or polishing the surface of the test material until the blowhole B is connected to the external environment as shown in FIG. 2(b). This allows the blowhole to be processed so as to connect to the external environment and not to have a closed structure. The processing method of providing the through hole is not particularly limited, but for example, a processing method of forming a through hole that reaches the blowhole from the surface of the test material using a micro drill or the like is included. In addition, the processing method of grinding or polishing is not particularly limited, but for example, a processing method of mechanically or chemically grinding or polishing the surface of the test material is included. In addition, if the blowhole is present near the surface of the test material, the blowhole may be removed by grinding or polishing. In addition, when the test material has a surface that has been cut as is, mechanical defects, such as work-hardened parts caused by an increase in dislocations or lattice defects, may be generated, and hydrogen may be trapped in the mechanical defects. Therefore, it is preferable to remove the surface by chemical polishing.
[0032] According to the above procedure, a test material for measuring the amount of diffusible hydrogen in a metal material having a weld is prepared. The test material prepared by the test material preparation method according to an embodiment of the present disclosure is suitable as a test material for measuring the amount of diffusible hydrogen, and is particularly suitable as a test material for evaluating delayed fracture properties.
[0033] <Method for measuring the amount of diffusible hydrogen> A method for measuring the amount of diffusible hydrogen in a metallic material having a welded portion according to one embodiment of the present disclosure includes a hydrogen introduction step of introducing hydrogen into a test material prepared by the above-mentioned test material preparation method, and a hydrogen amount measurement step of measuring the amount of hydrogen introduced into the test material in the hydrogen introduction step.
[0034] (Hydrogen introduction step) In the hydrogen introduction step, hydrogen is introduced into the test material prepared as described above. The hydrogen introduction method may be appropriately selected according to the purpose. Specific examples of the hydrogen introduction method include a cathode charge method in which the test material is used as a cathode and platinum or the like is used as an anode in an electrolyte, and an electric current is passed between the cathode and the anode to electrolyze the electrolyte, and the hydrogen generated at that time is introduced into the test material, and a hydrochloric acid immersion method in which the test material is immersed in a hydrochloric acid solution or the like. In addition, when it is desired to evaluate the amount of hydrogen introduced in an environment (actual environment) in which a metal material is actually used, the test material may be placed in the actual environment. Note that the test material after hydrogen is introduced in the hydrogen introduction step is preferably immersed in liquid nitrogen for storage. By immersing the test material in liquid nitrogen, it is possible to prevent the hydrogen introduced into the test material from being desorbed.
[0035] (Hydrogen amount measurement step) In the hydrogen amount measurement step, the amount of hydrogen (diffusible hydrogen amount) of the test material into which hydrogen has been introduced in the hydrogen introduction step is measured. The method for measuring the amount of hydrogen is not limited as long as it is a method capable of measuring the amount of hydrogen. For example, thermal desorption analysis can be used. Thermal desorption analysis is capable of analyzing extremely small amounts of hydrogen, and is therefore preferred as an analytical method for measuring the amount of diffusible hydrogen for evaluating the delayed fracture properties of metal materials. Note that, if the test material after hydrogen introduction in the hydrogen introduction step is stored in liquid nitrogen, it is preferred to measure the amount of hydrogen promptly after removing the test material from the liquid nitrogen.
[0036] <Evaluation method for delayed fracture properties> The evaluation method of delayed fracture properties according to an embodiment of the present disclosure includes an evaluation step of evaluating delayed fracture properties based on the amount of hydrogen (diffusible hydrogen amount) obtained by the above-mentioned method for measuring the amount of diffusible hydrogen. In the evaluation step, for example, when judging the superiority or inferiority of delayed fracture properties of a weld between test materials of different metal materials, the following evaluation may be performed for each test material. That is, for each test material, in the above-mentioned method for measuring the amount of diffusible hydrogen, the amount of diffusible hydrogen is measured when the hydrogen introduction environment (hydrogen introduction conditions) is made uniform in the hydrogen introduction step, and the values are compared to perform the evaluation. This is because it is generally considered that the more diffusible hydrogen a metal material has, the more likely delayed fracture is to occur. In order to perform a more accurate evaluation, it is preferable to measure the amount of diffusible hydrogen under hydrogen introduction conditions that cause cracks in the weld of the test material, and judge the delayed fracture properties of the test material.
[0037] <How to select metal materials> The method for selecting a metallic material according to an embodiment of the present disclosure includes a selection step for selecting a metallic material based on the delayed fracture property obtained by the delayed fracture property evaluation method described above. By performing the evaluation step on a metallic material having a welded portion, a relationship between the welding conditions and the delayed fracture property, for example, the amount of diffusible hydrogen when the hydrogen introduction environment is aligned in the hydrogen introduction step, can be obtained. Furthermore, the relationship may be obtained by changing the type of metallic material. Then, using these relationships, metallic materials can be classified. Then, in the selection step, for example, by evaluating the amount of diffusible hydrogen in the environment in which the metallic material is used, a metallic material suitable for use in the environment can be selected from the classification. Then, the selected metallic material can be shipped, etc.
[0038] <Method of manufacturing components> A method for manufacturing a member according to an embodiment of the present disclosure includes a welding step of manufacturing a member by at least welding a metal material selected by the metal material selection method. When manufacturing the member, for example, the metal material may be processed and then welded to form a member, or may be welded and then processed to form a member. The welding method in the welding step is not particularly limited, and for example, a known welding method can be applied. In addition, the processing is not particularly limited, and various types of metal processing such as molding processing can be used. In addition, the member is preferably an automobile part. EXAMPLES
[0039] The present disclosure will be specifically described below with reference to examples, although the present disclosure is not limited to the examples described below.
[0040] First, a metal material having a welded portion was produced by the following procedure: Steel plates A to C having the representative component composition shown in Table 1, a thickness of 1.6 mm, and a tensile strength of 1200 to 1500 MPa were prepared.
[0041] [Table 1]
[0042] First, three test pieces cut to 120mm x 30mm for each of steel plates A, B, and C were spot welded near the center. Spot welding was performed at room temperature using chrome copper DR-type electrodes with a tip diameter (tip diameter) of 6mm and a curvature radius of 40mm for both the lower and upper electrodes, with the electrodes always kept water-cooled. A current was applied so that the nugget diameter was 3√t (t: plate thickness), and a metal material (test specimen) with a weld was produced.
[0043] Test pieces were cut from the obtained specimens using a microcutter. The size of the test pieces was adjusted to match the volume ratio of the target weld metal. The test pieces were then chemically polished by immersing them in a mixed solution of hydrogen peroxide and oxalic acid.
[0044] (Step to identify blowhole location) For the obtained test material, the positions of blowholes were identified three-dimensionally using X-ray CT. In addition, the volume ratio of the weld metal in the test material was calculated using the images obtained by X-ray CT. The number of blowholes identified above and the calculated volume ratio of the weld metal in the test material are shown in Tables 2 and 3.
[0045] (Processing steps) Next, the blowholes identified in the step of identifying the blowhole positions were processed so that the blowholes would not have a closed structure. Specifically, a through hole was provided in the blowhole from the surface of the test material using a micro drill. However, for No. 1 and No. 2 in Table 2, the above processing was not performed, and for No. 3 in Table 2, the above processing was performed on some of the identified blowholes. For No. 6 in Table 2, the above processing was not performed because there was no blowhole in the welded part of the test material (reference example). In addition, whether or not the blowholes had a closed structure after the above processing was confirmed by using an X-ray CT scan of the test material after the above processing. Tables 2 and 3 show the number of blowholes with a closed structure present in the test material. In Tables 2 and 3, if the number of blowholes with a closed structure is 0, it is determined that processing was performed so that the blowholes would not have a closed structure, and the test material was passed.
[0046] (Hydrogen introduction step) Hydrogen was introduced into the test materials prepared as described above under the hydrogen introduction conditions shown in Tables 2 and 3. After hydrogen was introduced, the test materials were immediately immersed in liquid nitrogen and frozen for storage in order to prevent the introduced hydrogen from being desorbed.
[0047] (Hydrogen amount measurement step) Just before measuring the amount of hydrogen, the test material was quickly removed from the liquid nitrogen, and the amount of hydrogen (diffusible hydrogen) was measured by temperature-programmed desorption analysis using a low-temperature heating hydrogen analyzer. The temperature-programmed desorption analysis was performed in the temperature range of -50°C to 800°C at a heating rate of 200°C / h. The amount of diffusible hydrogen was calculated as a mass fraction (ppm by mass) by integrating the amount of hydrogen measured from -50°C to 200°C and dividing the integrated value of the amount of hydrogen by the mass of the test material. The amount of hydrogen (diffusible hydrogen) obtained for each test material is shown in Tables 2 and 3.
[0048] [Table 2]
[0049] [Table 3]
[0050] From Table 2, when the test material had blowholes with a closed structure (No. 1 to No. 3), the amount of diffusible hydrogen was 3.8 to 4.5 mass ppm. In contrast, when the blowholes with a closed structure were eliminated by processing (No. 4, No. 5), the amount of diffusible hydrogen was 2.3 to 3.2 mass ppm. In addition, the amount of diffusible hydrogen in the test material without blowholes (No. 6) was 2.7 mass ppm. From this, it can be seen that the amount of diffusible hydrogen was significantly reduced by eliminating the blowholes with a closed structure, and the amount of diffusible hydrogen was estimated to be high due to the presence of blowholes with a closed structure. It can also be seen that the amount of diffusible hydrogen can be evaluated with high accuracy by using test material without blowholes with a closed structure.
[0051] Furthermore, from Table 3, in test materials with a closed structure and no blowholes, if the volume ratio of the weld metal in the test materials was roughly the same, the obtained diffusible hydrogen amount values showed the following ranking: Steel plate A > Steel plate B > Steel plate C. It was also found that when the volume ratio of the weld metal in the test materials was 50% or more, the difference between steel types became more apparent.
[0052] On the other hand, when the delayed fracture properties of the welds of Steel Plate A, Steel Plate B, and Steel Plate C were evaluated using a conventional method (Patent Document 1), it was found that the delayed fracture resistance properties showed the following hierarchy: (superior) Steel Plate C > Steel Plate B > Steel Plate A (inferior).
[0053] From the above, it is considered that the steel sheet obtained by the method of the present disclosure with a larger amount of diffusible hydrogen is more likely to suffer from delayed fracture.
[0054] From the above, it can be said that the method disclosed herein can measure the amount of diffusible hydrogen in a metallic material having a welded portion with high accuracy and high reproducibility. Furthermore, it can be said that the method disclosed herein can be used as an index for evaluating the delayed fracture resistance of the metallic material, and can quantitatively and accurately evaluate the delayed fracture resistance. [Explanation of symbols]
[0055] 1 Metallic materials with welds 2. Weld metal 3 Test materials B Blowhole T through hole
Claims
1. A method for preparing a test material for measuring a diffusible hydrogen content of a metal material having a weld, comprising the steps of: A step of identifying a blowhole position in a test piece which is a metal material having a weld; a processing step of processing the blowhole identified in the step of identifying the blowhole position so that it does not have a closed structure, or of removing the blowhole.
2. The method for preparing a test material according to claim 1 , wherein a volume ratio of the weld metal in the test material is 50% or more.
3. A method for measuring the amount of diffusible hydrogen in a metal material having a weld, comprising: A hydrogen introduction step of introducing hydrogen into a test material prepared by the method for preparing a test material according to claim 1 or 2; A hydrogen amount measuring step of measuring the amount of hydrogen in the test material into which hydrogen has been introduced in the hydrogen introduction step.
4. A method for evaluating delayed fracture properties of a metallic material having a weld, comprising: A method for evaluating delayed fracture properties, comprising an evaluation step of evaluating delayed fracture properties based on the amount of diffusible hydrogen obtained by the method for measuring the amount of diffusible hydrogen according to claim 3.
5. A method for selecting a metallic material, comprising the steps of: A method for selecting a metallic material, comprising a selection step of selecting a metallic material based on the delayed fracture property obtained by the delayed fracture property evaluation method according to claim 4.
6. A method for manufacturing a component, comprising the steps of: A method for manufacturing a component, comprising a welding step of manufacturing the component by at least welding the metallic material selected by the metallic material selection method according to claim 5.
Citation Information
Patent Citations
Measuring device and measuring method of amount of diffusible hydrogen
JP2008261821A
Method for evaluating delayed fracture of metal material
JP2017187441A
Evaluation method of hydrogen embrittlement resistance
JP2018159701A
Method of preparing sample for analyzing absorbed hydrogen in steel, analyzing method of absorbed hydrogen in steel, prediction method of brittle deterioration caused by diffusible hydrogen in steel plate, and certification method of steel plate test result
JP2022072595A
High-strength steel sheet having excellent hydrogen brittleness resistance in weld zone and its production method
JP2007231373A
Cited By
Control method and system for laser hybrid welding
CN121289758A